Using Transcript Based Lesson Analysis to Analyze Students' Critical Thinking Skills on Hydrostatic Pressure - Nurmalasari, Santy; Hendayana, Sumar; Supriatna, Asep (FKIP Universitas Lampung, 2022)
This study aims to analyze the profile of students' critical thinking skills that appear during hydrostatic pressure learning with the discovery learning model in junior high school. The critical thinking skill indicator used is based on the Paul and Elder version. The method used in this research is descriptive qualitative. This research was conducted in one of the junior high schools in Sumedang Regency, West Java. The research subjects consisted of 16 students from class VIII. The instruments used are observation and video recording during the learning process. The collected data were analyzed using Transcript Based Lesson Analysis (TBLA). The results showed that during the learning process eight elements of reasoning and critical thinking skills could be observed, but the percentage was still small. The introductory session found four indicators of critical thinking skills activity with a percentage of 30.53%. In group discussion activities found eight indicators of critical thinking with a percentage of 40.27%. And in the closing session found five indicators of critical thinking skills activity with a percentage of 32.29%. The low achievement indicators of students' critical thinking skills are caused because students are still not accustomed to expressing what is on their minds and the teacher cannot still ask questions that encourage students to think. Activity analysis and dialogue during learning can be used as reflection material for teachers to evaluate and improve on further learning to make it better. Keywords: TBLA, discovery learning, critical thinking skills, hydrostatic pressure. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp519-528